Bismuth vanadate composite material and preparation method and application thereof

By adding cetyl trimethylammonium bromide and ferric nitrate nohydrate to the bismuth vanadate photocatalytic material, Fe2O3-BiVO4 composite material was prepared, which solved the problems of low photocatalytic activity of bismuth vanadate and complex preparation process, and achieved efficient catalytic conversion of carbon dioxide.

CN119588370APending Publication Date: 2025-03-11LIAONING UNIVERSITY OF PETROLEUM AND CHEMICAL TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411786786.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing bismuth vanadate photocatalytic materials have problems with high photocarrier recombination rate and low catalytic activity in carbon dioxide treatment, and the preparation process of the existing improved methods is complex, with high energy consumption and cost.

Method used

By reacting bismuth nitrate pentahydrate and ammonium metavanadate in dilute nitric acid and dilute sodium hydroxide solution, cetyl trimethyl ammonium bromide was added, and then stirred by ultrasonic and heating, a bismuth vanadate composite material Fe2O3-BiVO4 with a large specific surface area was prepared.

Benefits of technology

The catalytic activity and selectivity of bismuth vanadate composite materials are improved, the photogenerated electron-hole recombination rate is reduced, the conversion rate of carbon dioxide is improved, and the preparation process is mild, and the energy consumption and cost are low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588370A_ABST
    Figure CN119588370A_ABST
Patent Text Reader

Abstract

The invention relates to an inorganic composite material as well as a preparation method and application thereof, in particular to a bismuth vanadate composite material as well as a preparation method and application thereof. The preparation method of the bismuth vanadate composite material comprises the following steps: 1) dissolving bismuth nitrate pentahydrate in dilute nitric acid to form a solution A; dissolving ammonium metavanadate in a dilute sodium hydroxide solution to form a solution B; 2) slowly dripping the solution B into the solution A, and continuously stirring to obtain a mixed solution C; (3) adding hexadecyl trimethyl ammonium bromide into the mixed solution C, continuously stirring for 0.5-1 hour to obtain a precursor solution, and heating the precursor solution; 4) cooling the precursor solution to room temperature, separating to obtain a solid product, alternately washing with pure water and ethanol for 3 times, and drying to obtain bismuth vanadate; and 5) mixing bismuth vanadate with ferric nitrate nonahydrate and water, performing ultrasonic treatment for 0.5-1 hour, and heating and stirring until the liquid is evaporated to dryness. The composite material obtained by the invention has a larger specific surface area, can provide more active sites, and improves the conversion rate of carbon dioxide and the selectivity and stability of a catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an inorganic composite material and a preparation method and application thereof, and in particular to a bismuth vanadate composite material and a preparation method and application thereof. The obtained bismuth vanadate composite material can be applied to photocatalytic reduction of CO2. Background Art

[0002] With the continuous progress and development of human society, more and more fossil fuels are consumed, resulting in an increase in the carbon dioxide content in the atmosphere year by year. This has led to a rise in global temperatures, triggering a series of environmental problems, including global warming, an increase in extreme weather events, melting glaciers and rising sea levels. In order to mitigate climate change, the international community has taken a series of measures, including improving energy efficiency, developing renewable energy, promoting low-carbon technologies, implementing carbon capture and storage technologies, and afforestation, to reduce the emission of greenhouse gases such as carbon dioxide. As a renewable energy source, solar energy is not only abundant in resources, cheap and clean, but also has no pollution to the environment. Using abundant solar energy to convert CO2 into high-value-added chemical products or hydrocarbon fuels can solve both energy and environmental problems. It provides a feasible strategy for mitigating climate change and developing renewable energy.

[0003] In recent years, bismuth vanadate photocatalytic materials have been widely used in carbon dioxide treatment. As a semiconductor material, bismuth vanadate has three types of crystal structures. Its monoclinic scheelite-type bismuth vanadate has a narrow band gap and has large absorption in the visible light region, which can make full use of solar energy to reduce carbon dioxide. However, pure bismuth vanadate photogenerated carriers are easy to recombine and have low catalytic activity. Therefore, reducing the photogenerated electron-hole recombination rate and improving the photocatalytic activity of bismuth vanadate are the main challenges faced by photocatalyst development. Patent CN101318700B provides a method of using hexadecyltrimethylammonium bromide as a structure-directing agent to achieve local regulation of the micromorphology of bismuth vanadate by adjusting the hydrothermal temperature, thereby reducing the recombination rate of photogenerated carriers and improving photocatalytic activity. However, the absorption band edge of bismuth vanadate prepared by this method is 540-550 nanometers, the band gap is large, and higher energy photons are required to excite electronic transitions. Patent CN118454719A provides a method for preparing molybdenum disulfide / nitrogen-doped carbon quantum dots / nitrogen-doped vanadium vacancy defect state bismuth vanadate nanosheets. Although the bismuth vanadate composite material prepared by the method can effectively inhibit the recombination of photogenerated carriers of bismuth vanadate, the preparation process of the composite catalyst is complicated, and the energy consumption and cost are high. Patent CN112058257B provides a preparation method of a photocatalyst doped with rare earth Tb and bismuth vanadate, which adopts a liquid phase precipitation method. The preparation method is simple and mild, and the photodegradation efficiency of the photocatalyst doped with rare earth Tb and bismuth vanadate is as high as 99%, but rare earth elements are less in nature and are not easy to obtain. Therefore, it is very necessary to provide a green, convenient and efficient preparation method for improved bismuth vanadate. Summary of the invention

[0004] The present invention provides a bismuth vanadate composite material and a preparation method and application thereof. The obtained bismuth vanadate composite material has a large specific surface area and can provide more active sites, thereby ultimately improving the conversion rate of carbon dioxide and the selectivity and stability of the catalyst.

[0005] According to a first aspect of the present invention, a method for preparing a bismuth vanadate composite material is provided, comprising the following steps:

[0006] 1) dissolving bismuth nitrate pentahydrate in dilute nitric acid to form solution A; dissolving ammonium metavanadate in dilute sodium hydroxide solution to form solution B;

[0007] 2) slowly dripping the solution B obtained in step 1) into the solution A, and continuously stirring to obtain a mixed solution C;

[0008] 3) Add hexadecyltrimethylammonium bromide to the mixed solution C obtained in step 2), continue stirring for 0.5h to 1h to obtain a precursor solution, and heat the precursor solution;

[0009] 4) cooling the precursor solution after the heating treatment in step 3) to room temperature, separating and obtaining a solid product, washing it alternately with pure water and ethanol, and drying it to obtain bismuth vanadate;

[0010] 5) The bismuth vanadate obtained in step 4) is mixed with ferric nitrate nonahydrate and water, subjected to ultrasonic treatment for 0.5 h to 1 h, and heated and stirred until the liquid is evaporated to dryness, thereby obtaining a bismuth vanadate composite material.

[0011] Optionally, in step 1), the molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 1:1.

[0012] Optionally, in step 1), the concentration of dilute nitric acid is 1 mol / L to 1.2 mol / L, and the concentration of dilute sodium hydroxide is 1 mol / L to 1.2 mol / L.

[0013] Optionally, the pH value of the mixed solution C in step 2) is 6 to 6.5.

[0014] Optionally, in step 3), the mass of hexadecyltrimethylammonium bromide added is 1.0% to 1.2% of the mass of bismuth nitrate pentahydrate, and the stirring speed is 1000 r / min to 1200 r / min.

[0015] Optionally, in step 3), the precursor solution is heated to a temperature of 190° C. to 195° C. for 6 h to 6.5 h.

[0016] Optionally, in step 4), the drying temperature is 80° C. to 85° C., and the drying time is 11 h to 12 h.

[0017] Optionally, in step 5), the molar ratio of ferric nitrate nonahydrate to bismuth vanadate is 1:9, and the heating temperature is 90° C. to 95° C.

[0018] The present application also provides a technical solution of the second aspect, namely, a bismuth vanadate composite material, wherein the bismuth vanadate composite material is prepared by any of the aforementioned preparation methods.

[0019] The present application also provides a third technical solution, namely, application of the bismuth vanadate composite material, wherein the application is to use it as a photocatalytic material for photocatalytic reduction of CO2.

[0020] The bismuth nitrate pentahydrate, ammonium metavanadate, nitric acid, sodium hydroxide, and hexadecyl trimethyl ammonium bromide used in the present invention can all be obtained commercially. The reaction conditions used are, for example, a heating temperature of 190°C to 195°C, a heating time of 6h to 6.5h, and a pH of 6 to 6.5. The hexadecyl trimethyl ammonium bromide used has good solubility in the aqueous phase system, can effectively reduce the surface tension of the solution, and make the reaction system more stable, which is conducive to promoting the degree of preferential orientation growth of bismuth vanadate along the (040) crystal plane to achieve preferential orientation growth. Fe is loaded onto the surface of bismuth vanadate in the form of Fe2O3 by an impregnation method to form a heterojunction structure with it, thereby reducing the recombination rate of photogenerated carriers of bismuth vanadate.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) By utilizing the spatial confinement and guiding effect of CTAB, the local controllability of the micromorphology of bismuth vanadate can be achieved by regulating various reaction conditions.

[0023] (2) The bismuth vanadate composite material provided by the present invention, namely the Fe2O3-BiVO4 composite material, has a suitable bandgap width and can generate catalytically active electron-hole pairs under appropriate illumination. When CO2 is adsorbed on the surface of the composite material, the electron-hole pairs are captured to convert CO2 into CO, thereby having good application prospects in the efficient use of solar energy to catalytically convert greenhouse gas CO2 to prepare high-value fuels and / or chemicals. Moreover, the Fe2O3-BiVO4 composite material of the present invention, as a photocatalytic material, has mild reaction conditions for catalytically converting greenhouse gas CO2, high degradation efficiency, and significant effect, and the material after catalytic degradation is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the reactor structure diagram of the evaluation device 3;

[0025] Figure 2 TEM images of Example 1 (left) and Example 2 (right);

[0026] Figure 3is the X-ray diffraction pattern of Example 1 and Example 2;

[0027] Figure 4 It is the UV-vis diagram of Example 1 and Example 2;

[0028] Figure 5 PL spectra of Example 1 and Example 2;

[0029] Figure 6 It is a comparison chart of the photocatalytic reduction of carbon dioxide performance of Example 1, Example 2 and the comparative example. DETAILED DESCRIPTION

[0030] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.

[0032] It should be noted that the terms "first", "second", etc. in the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0033] The bismuth vanadate and bismuth vanadate composite materials obtained in the present application can be evaluated by various existing methods to illustrate their catalytic effect on CO2, and can also be evaluated using any of the following exemplified evaluation devices.

[0034] Evaluation device 1

[0035] (Jiang Yuting, Xu Hong, Zhong Yi, et al. Preparation of MCM-41 / NH2-MIL-101 (Fe) composite materials and their photocatalytic reduction of CO2 performance [J]. Modern Chemical Industry, 2024, 44 (S2): 155-160.), Jiang Yuting et al. dissolved carbon dioxide in a mixture of H2O and TEOA, and set the reaction conditions to 25 ° C and 400 r / min. After dark treatment for 30 minutes, a 300W xenon lamp was turned on and illuminated for 5 hours. Samples were taken and analyzed once every 1 hour, and the products were detected and analyzed using a liquid chromatograph, and the yield was calculated by the peak area.

[0036] Evaluation device 2

[0037] Patent CN220609831U provides a photocatalytic reduction of carbon dioxide reactor, wherein a transparent container cover is provided at the container mouth, a light source is located directly above the transparent container cover and directly irradiates the transparent container cover, a water dropper is connected to the inner side of the transparent container cover, an air inlet is provided on one side of the lower end of the reactor, and an air outlet is provided on the other side, one end of a circulation pipe is connected to the air inlet, and the other end is connected to the air outlet, a circulation fan is installed in the circulation pipe, a gas filling pipe is connected to the circulation pipe, a rubber stopper is plugged at the gas filling pipe, a catalyst placement bag is placed inside the reactor, the catalyst placement bag is located directly below the water dropper, a sampling tube is connected to the lower end of the reactor, and a rubber stopper is plugged at the sampling tube.

[0038] Evaluation device 3

[0039] like Figure 1 As shown, the photocatalytic reduction of carbon dioxide reactor is a laboratory-made 100mL quartz reactor. A quartz window is set on the top of the reactor (with a sealing ring 1 and a head 2 on the top) for irradiation through the light source above the container. The reaction is carried out at room temperature and normal pressure. A 300W xenon lamp is used to simulate visible light. The lamp is located about 10cm above the reaction device. In the homemade quartz reactor, 10mg of photocatalyst 7 is evenly dispersed on the metal mesh 3 so that the photocatalyst can fully contact with carbon dioxide gas in the reaction chamber 6. CO2 gas enters from the air inlet 4, and its CO gas generation rate is detected from the air outlet 5. Under light irradiation, the reactor is sealed, and humid carbon dioxide gas is passed through at a flow rate of 0.2L / min for washing. After washing is repeated 3 times, ensure that the air in the reactor is exhausted. After the air is exhausted, the reactor outlet is sealed with a silicone rubber plug and ventilation is continued for 5min. The test sampling point is 0h (before turning on the light), and 1mL of gas is taken every 1h thereafter. The composition and content of the product are detected by gas chromatograph, and the total reaction time is 4h.

[0040] Among the existing evaluation devices and the above-mentioned example evaluation devices, the following Examples 1 to 2 obtained in this application and the corresponding comparative examples can be evaluated using existing conventional evaluation devices or any of the above-mentioned evaluation devices in the evaluation of CO2 catalytic effect.

[0041] Example 1

[0042] Dissolve 1mmol of bismuth nitrate pentahydrate in 30mL of 1mol / L-1.2mol / L nitric acid to form solution A. Disperse 1mmol of ammonium metavanadate in 30mL of 1mol / L-1.2mol / L sodium hydroxide solution to form solution B. Slowly drip solution B into solution A and stir continuously to form a yellow emulsion. Adjust the pH value to 6-6.5 to obtain mixed solution C. Add hexadecyltrimethylammonium bromide in an amount of 1.0%-1.2% of the mass of bismuth nitrate pentahydrate to mixed solution C and continue stirring for 0.5h-1h to obtain a precursor solution. The obtained precursor solution was transferred to a 100 mL hydrothermal reactor lined with polytetrafluoroethylene, sealed and placed in a 190°C to 195°C oven for constant temperature reaction for 6h to 6.5h, cooled to room temperature and separated to obtain a solid product, which was washed alternately with pure water and ethanol, dried at 80°C to 85°C for 11h to 12h, and the dried powder was fully ground with a mortar to obtain a bismuth vanadate photocatalytic material. The various detection properties of the obtained bismuth vanadate in Example 1 are as follows: Figures 2 to 5 As shown, the CO2 catalytic effect is measured by any of the above evaluation devices, and the evaluation results are averaged. Figure 6 .

[0043] Example 2

[0044] Dissolve 1mmol of bismuth nitrate pentahydrate in 30mL of 1mol / L-1.2mol / L nitric acid to form solution A. Disperse 1mmol of ammonium metavanadate in 30mL of 1mol / L-1.2mol / L sodium hydroxide solution to form solution B. Slowly drip solution B into solution A and stir continuously to form a yellow emulsion. Adjust the pH value to 6-6.5 to obtain a mixed solution C. Add hexadecyltrimethylammonium bromide at a mass of 1.0%-1.2% of the mass of bismuth nitrate pentahydrate to the mixed solution C, and continue stirring for 0.5h-1h to obtain a precursor solution. Transfer the obtained precursor solution to a 100mL hydrothermal reactor lined with polytetrafluoroethylene, seal it, and place it in a 190℃-195℃ oven for constant temperature reaction for 6h-6.5h, then cool it to room temperature and separate the solid product. Wash the obtained solid product alternately with pure water and ethanol, dry it at 80℃-85℃ for 11h-12h, and grind the dried powder with a mortar for later use. According to the molar ratio of ferric nitrate nonahydrate to bismuth vanadate of 1:9, weigh ferric nitrate nonahydrate and bismuth vanadate, pour the weighed bismuth vanadate powder and ferric nitrate nonahydrate into a beaker at the same time, add 100mL of water to the beaker, ultrasonicate for 0.5h~1h, put the beaker into a 90℃~95℃ constant temperature heating stirrer and stir until the liquid in the beaker is completely evaporated and then stop heating. The obtained product is a bismuth vanadate composite material. The various detection properties of the bismuth vanadate composite material obtained in Example 2 are as follows Figures 2 to 5As shown, the CO2 catalytic effect is evaluated by any of the above evaluation devices, and the evaluation results are averaged. Figure 6 .

[0045] Comparative Example 1 of Example 1

[0046] (Zhu Yongqiang, Chen Fangyan, Lu Yifeng, et al. Ionic liquid-assisted hydrothermal synthesis of BiVO4 catalyst and its visible light catalytic activity [J]. Journal of Environmental Engineering, 2015, 9(04): 1875-1880.) Zhu Yongqiang et al. prepared BiVO4 by 1-butyl-3-methylimidazolium bromide ([Bmim]Br) ionic liquid-assisted hydrothermal synthesis. The operation is as follows: 5mmol Bi(NO3)·5H2O is dissolved in 20mL 4mol / L HNO3 solution to obtain solution A. 5mmol NH4VO3 is dissolved in 20mL deionized water to form solution B. After mixing solutions A and B, adjust the pH to the desired value under magnetic stirring, add a certain amount of 1-butyl-3-methylimidazolium bromide ionic liquid, and then transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner and react for a certain time at a set temperature. After the reaction is completed, the mixture is cooled to room temperature, filtered under reduced pressure, and the product is fully washed with ethanol and deionized water and then transferred to a forced air drying oven for drying at 80° C. for 4 h. The synthesis process of the ionic liquid required in this process is complicated and the cost is higher than that of the hexadecyltrimethylammonium bromide used in this application.

[0047] The method, innovation and technical effect disclosed in the present invention are essentially different from those of the comparative example.

[0048] Comparative Example 2 of Example 1

[0049] (Xiao Qianghua, Zhu Yi, Guo Jia, et al. A new low-temperature solid-phase method for selective preparation of monoclinic bismuth vanadate [J]. Journal of Inorganic Chemistry, 2011, 27(01): 19-24.) Xiao Qianghua et al. used a low-temperature solid-phase method to prepare monoclinic BiVO4 as follows: 5.0mmol (2.45g) Bi(NO3)·5H2O and 5.0mmol (0.58g) NH4VO3 were mixed evenly and then fully ground in an agate mortar until a reddish brown slurry was formed. After grinding, the reddish brown slurry was transferred to an alumina crucible, and then placed in an oven and dried at 120°C for 12h. After the reaction was completed, the product was taken out from the crucible, washed with distilled water and anhydrous ethanol 3 times each, and the obtained product was dried at 60°C in a vacuum for 4h after centrifugation to obtain a bismuth vanadate sample. The spherical microparticles of bismuth vanadate prepared by this process showed impurity peaks in the XRD characterization, which would reduce the catalytic performance of bismuth vanadate.

[0050] The method, innovation and technical effect disclosed in the present invention are essentially different from those of the comparative example.

[0051] Comparative Example 1 of Example 2

[0052] (Zhang Lihong. Preparation and photocatalytic performance of Fe2O3 / BiVO4 composite photocatalyst [J]. Guangdong Chemical Industry, 2015, 42(19): 30-31.), Zhang Lihong et al. deposited Fe2O3 nanoparticles on the surface of BiVO4 by in-situ hydrothermal deposition method, the operation is as follows: weigh 0.5mmol BiVO4 powder, disperse it with deionized water at room temperature for 10min, add 1.0mmol NaOH and 0.8mmol Fe(NO3)3 in turn, continue stirring for 20min, transfer to a polytetrafluoroethylene reactor and seal it, react at 180℃ for 12h, cool to room temperature, separate and wash with deionized water and anhydrous ethanol several times, dry at 60℃, and then calcine at 400℃ for 2h to obtain Fe2O3 / BiVO4 composite photocatalyst. This process reaction requires high temperature and takes a long time.

[0053] The method, innovation and technical effect disclosed in the present invention are essentially different from those of the comparative example.

[0054] Comparative Example 2 of Example 2

[0055] (Liu N, Ouyang D, Cai Y, et al. Heterostructured Fe2O3 / BiVO4nano-photocatalyst for the reduction of nitroarenes into amines[J]. Ceramics International, 2020, 46(15):24534-24543.), Liu et al. prepared Fe2O3 / BiVO4 by ultrasonic precipitation, and the operation was as follows: 500mg BiVO4 was dispersed in 100mL deionized water, and then the calculated weight percentage of FeCl3·6H2O and sodium dodecyl sulfate were added, and then ultrasonicated at 85°C for 2h. The formed precipitate was centrifuged and washed with water, and then the excess water was removed with ethanol. The wet solid was placed in an oven and heated at 60°C for 24h. The dried solid was calcined at 300°C for 4h to remove the organic content. This method requires high temperature, complex operation, high energy consumption and long time.

[0056] The method, innovation and technical effect disclosed in the present invention are essentially different from those of the comparative example.

[0057] Comparative Example 3 of Example 2

[0058] Patent 117181233A provides a method for preparing Fe2O3 / BiVO4 by photodeposition. The operation is as follows: add BiV04 and PVP to water, stir to obtain a suspension, control the pH, add ferrous chloride to the suspension, stir in the dark, add potassium iodate, and react for 3 hours under a xenon lamp. After the reaction is completed, collect the precipitate, wash the product with organic matter and distilled water, and vacuum dry to obtain Fe2O3 / BiVO4. The applicant used the method of this application to prepare the obtained bismuth vanadate, reproduced the Fe2O3 / BiVO4 according to the method provided by the above patent, and used any of the above evaluation devices to evaluate the CO2 catalytic effect of the catalyst obtained in Comparative Example 3. The evaluation results were averaged, see Figure 6 .

[0059] Comparative Example 4 of Example 2

[0060] Patent CN101318700B provides a method for preparing bismuth vanadate. The bismuth vanadate prepared according to the operation is used to obtain Fe2O3 / BiVO4 using step 5) of the preparation method of the present application, and the catalyst obtained in comparative example 4 is used to evaluate its CO2 catalytic effect using any of the above-mentioned evaluation devices, and the evaluation results are averaged. Figure 6 .

[0061] Comparative Example 5 of Example 2

[0062] Patent CN117208958A provides a method for preparing bismuth vanadate. The bismuth vanadate prepared according to the operation is used to obtain Fe2O3 / BiVO4 using step 5) of the preparation method of the present application, and the catalyst obtained in comparative example 5 is used to evaluate its CO2 catalytic effect using any of the above-mentioned evaluation devices, and the evaluation results are averaged. Figure 6 .

[0063] from Figure 6 It can be seen that the bismuth vanadate composite material obtained in the present application has a better catalytic effect on CO2 (higher CO gas production rate) than the bismuth vanadate composite material obtained by the existing preparation method due to the use of specific process parameters. It can be seen that the bismuth vanadate composite material obtained in the present application has a lower recombination rate of photogenerated carriers, which can effectively promote the transfer of electrons and protons to CO2, thereby improving the efficiency of the catalytic reaction.

[0064] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a bismuth vanadate composite material, characterized in that: The following steps are involved: 1) dissolving bismuth nitrate pentahydrate in dilute nitric acid to form solution A; Dissolving ammonium metavanadate in a dilute sodium hydroxide solution to form solution B; 2) slowly dripping the solution B obtained in step 1) into the solution A, and continuously stirring to obtain a mixed solution C; 3) Add hexadecyltrimethylammonium bromide to the mixed solution C obtained in step 2), continue stirring for 0.5h to 1h to obtain a precursor solution, and heat the precursor solution; 4) cooling the precursor solution after the heating treatment in step 3) to room temperature, separating and obtaining a solid product, washing it alternately with pure water and ethanol, and drying it to obtain bismuth vanadate; 5) The bismuth vanadate obtained in step 4) is mixed with ferric nitrate nonahydrate and water, subjected to ultrasonic treatment for 0.5 h to 1 h, and heated and stirred until the liquid is evaporated to dryness, thereby obtaining a bismuth vanadate composite material.

2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 1:

1.

3. The preparation method according to claim 1, characterized in that: In step 1), the concentration of dilute nitric acid is 1 mol / L to 1.2 mol / L, and the concentration of dilute sodium hydroxide is 1 mol / L to 1.2 mol / L.

4. The preparation method according to claim 1, characterized in that: The pH value of the mixed solution C in step 2) is 6 to 6.

5.

5. The preparation method according to claim 1, characterized in that: In step 3), the mass of cetyltrimethylammonium bromide added is 1.0% to 1.2% of the mass of bismuth nitrate pentahydrate, and the stirring speed is 1000 r / min to 1200 r / min.

6. The preparation method according to claim 1, characterized in that: In step 3), the precursor solution is heated to a temperature of 190° C. to 195° C. for 6 h to 6.5 h.

7. The preparation method according to claim 1, characterized in that: In step 4), the drying temperature is 80° C. to 85° C., and the drying time is 11 h to 12 h.

8. The preparation method according to claim 1, characterized in that: In step 5), the molar ratio of ferric nitrate nonahydrate to bismuth vanadate is 1:9, and the heating temperature is 90°C to 95°C.

9. A bismuth vanadate composite material, characterized in that: The bismuth vanadate composite material is prepared by any one of the preparation methods described in Claims 1 to 8.

10. Application of bismuth vanadate composite material, characterized in that: The application is to use it as a photocatalytic material for photocatalytic reduction of CO2.

Citation Information

Patent Citations

  • Bismuth vanadate powder and preparation method thereof

    CN101318700B

  • Rare Earth Tb-Doped Bismuth Vanadate Photocatalyst and Its Preparation Method

    CN112058257B

  • High-activity defect-state bismuth vanadate nanosheet as well as preparation method and application thereof

    CN118454719A